Strategi Formulasi: Analisis Situasi dan Strategi Bisnis dalam Menciptakan Keunggulan Bersaing Perusahaan - Sinarwaty; Rian Rinaldi; Ikbal Ikbal; Ahmad Adnan Wirapraja (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This article presents a comprehensive transformation of Chapter 6 of Strategic Management and Business Policy (2011) into an Indonesian-language scientific journal article format. The chapter focuses on strategy formulation through situational analysis (SWOT and strategic factor summary) and the development of alternative business strategies. Qualitative research methods are used by systematically analyzing the content of Chapter 6 and reorganizing the material into a standard article framework (Introduction, Literature Review, Methods, Results, Discussion, Conclusion, Recommendations, References). The research results synthesize key points: identification of Strengths-Weaknesses-Opportunities-Threats, review of the company's mission and objectives, use of the TOWS Matrix to formulate alternative strategies, and presentation of key business strategies such as cost leadership, differentiation, and focus. The discussion addresses the interpretation of the findings, practical implications for managers, and limitations such as subjectivity in assessing strategic factors. This article attempts to fill the literature gap by presenting a combined framework of strategy tools in the context of Indonesian strategic management.